(untitled) - Tintin Sukartini; Yulia Indah Permata Sari (University of Ostrava, 2021)
Aim: To explore the impact of mastectomy on the body image of women with breast cancer. Design: A qualitative study with a phenomenological approach. Methods: Thirty women (n = 30) with post-mastectomy breast cancer were obtained through a purposive sampling technique. Data were collected using in-depth and semi-structured individual interviews to explore the experiences of the participants and the meanings they attribute to them. The data was analysed using the Van Manen method and with the help of NVivo 12 software. Results: Three main themes were identified in this study: "breast meaning", "self-concept", and coping strategies for women after mastectomy. Breasts are interpreted as a symbol of female status that reflects femininity and attractiveness. Mastectomy can cause changes in appearance, which can affect women's body image, self-concept, and social interaction. Emotional intensive coping and problem-solving intensive coping are coping strategies used by women after mastectomy. Conclusion: Breasts are synonymous with femininity, beauty, and attractiveness. Therefore, many women feel that they have lost their femininity and self-confidence after losing their breasts due to mastectomy.